The Development of Islamic-Based Pancasila and Civic Education Curriculum at Junior High School: Research at Junior High Schools in Cluster 5 Bandung Regency - Teguh Prayitno; Agus Salim Mansyur; Adang Hambali; Yuyun Nurul'aen (Syntax Corporation Indonesia, 2022)
This research departs from an idea of how to develop an Islamic-based Civics curriculum that can improve morality (character building or character). The research conductedat SMPN 1 Cileunyi, SMPN 1 Cilengkrang, and SMPN 2 Cimenyan. An Islamic-based Civics Curriculum development design can inspire independent learning in a student-centric learning process and an Islamic teacher. The core values Islamic values into goals, programs, implementation, and evaluation. The primary purpose of this study was to determine the implications of Islamic-based Civics Curriculum Development in Junior High Schools that internalize Islamic values. This research used qualitative research and development, a process or steps to develop a new product or improve an existing product, which can be accounted for. Data collection techniques were obtained using library research, observation, interviews, questionnaires, and documentation studies. The result shows the implementation of Islamic-based Civics curriculum is based on the Thirteenth Curriculum, yet, or although there are still embryos of Islamic religious, moral values, teachers provide spiritual support in the learning process; The teaching resources are indeed less mastered on religious material so that teachers are needed who have two competencies, namely the competence of Civics and religious material